Gramsci in English - Buttigieg, Joseph A. (International Gramsci Journal, 2023)
The article retraces the how Gramsci’s major writings, mainly though not exclusively from the Prison Notebooks and then the Prison Letters, were made available to Anglophone readers. The main process got underway in the later 1950s in the attempt to present a non-dogmatic Marxism. As such, a major contribution came somewhat later from another source, John Cammett’s 1967 book Antonio Gramsci and the Origins of Italian Communism. The British “New Left Review” was instrumental around this time in publishing some material and paving the way for the influential 1971 anthology Selections from the Prison Notebooks, followed by an English version of Giuseppe Fiori’s biography, Antonio Gramsci: Life of a Revolutionary and by selections in the late 1970s from the pre-prison writings, namely journalistic articles and other political interventions; this was integrated by a Cambridge University Press volume published in 1994. The 1970s saw partial translations of the Prison Letters, and a full version in 1994. In the meantime a volume Selections from Cultural Writings appeared in the mid-80s and Further Selections from the Prison Notebooks in 1995, preceded somewhat earlier by the first volume of Buttigieg’s own integral translation of Valentino Gerratana’s 1975 critical edition of the Notebooks, now interrupted as work was proceeding beyond Volume 3. A recent addition in volume form is A Great and Terrible World. The PrePrison Letters; the title’s opening phrase is taken from Kipling, and was often used by Gramsci and his wife, Julija (Jul’ka), in the letters they exchanged before Gramsci’s arrest.